COMPARISON BETWEEN THE EFFICACY OF 9 % HYPERTONIC SODIUM CHLORIDE SOLUTION, PENTOSTAM AND SILVER NITRATE FOR TREATMENT OF CUTANEOUS LEISHMANIASIS: MOHAMMED A. KADIR AND HAYDER A. EL-GORBAN - KADIR, MOHAMMED A. (The Iraqi Journal of Veterinary Medicine, 2006)
The study was conducted on 107 patients of cutaneous leishmaniasis, fromDour town, Salahadeen province attending the Dermatology Department ofSaddam General Hospital, Tikrit.Patients were divided to 4 groups for purpose of treatment and comparison,followed up for two months duration.Group A: treated with intralesional hypertonic sodium chloride solution (9 %HSCS).Group B: treated with intralesional pentostam injection, 1 cc. per day for 6consecutive days.Group C: treated with silver nitrate cauterization one to two doses of three daysinterval.Group D: left without treatment as a control group.It was found that the efficacy of 9% hypertonic sodium chloride solution andpentostam were 94% and silver nitrate was 78%. No patient cured amonguntreated control group.It was concluded that the efficacy of sodium chloride solution and pentostamwas greater than silver nitrate solution.